2021
DOI: 10.1515/freq-2020-0217
|View full text |Cite
|
Sign up to set email alerts
|

DEMUX with low crosstalk and compact channel drop filter based on photonics crystals ring resonator with high quality factor

Abstract: The optical components based on photonic crystal had a wide range of applications fields these last years. In this work, we propose a configuration of photonic crystal structure of Channel Drop Filter (CDF). The proposed filter study by finite difference numerical method in the time domain FDTD makes it possible to ensure an average detected modal transmission rate of 95.30%, an average quality factor of order 3149.12 and a compact size of 144.65 μm2 with high sensitivity to small variation of refractive index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Currently, the best choice is to use optical communications, which further con rms the inevitability of the migration from electronics to optics and photonics. Consequently, these speci c optical networks consist of optical bers [1,2], waveguides [3,4], lters [5,6], demultiplexers [7,8], logic gates [9][10][11], adders [12], decoders and encoders [13][14][15], sensors and biosensors [16,17]. It has been demonstrated that all the mentioned optical devices can be realized using photonic crystals (PCs).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the best choice is to use optical communications, which further con rms the inevitability of the migration from electronics to optics and photonics. Consequently, these speci c optical networks consist of optical bers [1,2], waveguides [3,4], lters [5,6], demultiplexers [7,8], logic gates [9][10][11], adders [12], decoders and encoders [13][14][15], sensors and biosensors [16,17]. It has been demonstrated that all the mentioned optical devices can be realized using photonic crystals (PCs).…”
Section: Introductionmentioning
confidence: 99%